The accuracy of ultrasensitive PSA in predicting disease progression after radical prostatectomy - Seikkula, Heikki; Hyysalo, Jaakko; Hogerman, Mikael; Bostrom, Peter J.; Ettala, Otto (WILEY, 2025)
Objectives: To assess the role of ultrasensitive PSA values (usPSA) after radical prostatectomy in predicting the subsequent biochemical recurrence (BCR).
Material and methods: The study included 1836 patients who underwent open or robot-assisted RP at Turku University Hospital between 2003 and 2018. Exclusion criteria involved patients with adjuvant treatments and those who did not reach a PSA nadir <0.1 ng/ml, resulting in a final cohort of 1313 patients. The prognostic impact of the optimal usPSA nadir cut-off value 6 months after RP was investigated to predict subsequent BCR for the whole cohort (N = 1313). The optimal usPSA cutoff value was determined for patients at 3-5 years post-surgery (N = 806) and beyond 5 years (N = 493) of follow-up. We used the area under the curve (AUC) calculation and the Kaplan-Meier method.
Results: In a cohort with a median age of 64, primarily featuring Gleason score 7 prostate cancer. uPSA nadir of 0.01 ng/ml (AUC = 0.80) at the first monitoring post- surgery emerged as the optimal cut-off for identifying subjects at low (80%) or high (20%) risk of BCR within the first 3 years. Beyond this period, uPSA values during the first 3 [(AUC = 0.89; 3-5 years post-surgery) and (AUC = 0.81; beyond 5 years)] and 5 post-surgery years (AUC = 0.85) outperformed uPSA nadir in predicting subsequent BCR. Notably, EAU-defined high-risk patients with low uPSA nadir maintained substantial BCR-free survival.
Conclusion: In conclusion, a low usPSA predicts minimal BCR risk over the next 2- 3 years post-measurement. Patients with low usPSA can benefit from reduced post- surgery PSA monitoring at 2- to 3-year intervals without compromising outcomes. This strategic approach optimizes resource allocation in busy urological outpatient clinics, especially valuable in publicly reimbursed healthcare systems like Finland.